Theoretical and methodological aspects of measuring social cohesion (Economics and region, 2023)
The concept of social cohesion reflects the trends and results of social, economic, political, cultural processes, combining the system of goals, tasks and conditions of the external and internal environment. Today, social cohesion is considered as one of the priority concepts of social development, focused on integration, overcoming, smoothing, and erasing inequality and unevenness in all its manifestations, limitations of sustainable social development with the aim of achieving homogeneity, stability of the social system and harmonious social development. The purpose of the study is to generalize and develop the theoretical and methodological aspects of measuring social cohesion. The generalization of the main approaches to the measurement of social cohesion made it possible to distinguish the European and harmonization approaches. The European approach to understanding and measuring social cohesion is mostly focused on access to social rights in a fair and/or egalitarian way; income and welfare. The harmonization approach is focused on the understanding of social cohesion, first of all, as a common goal and trust between members of a certain social group or region, as well as the willingness of members of a social group to interact and cooperate for the sake of prosperity, progress and development. Thus, we associate the existence of a number of ways of measuring this difficult-to-formalize process with the multidimensional and interdisciplinary nature of the application of this concept. Based on the morphological analysis of the directions for measuring social cohesion, the seven most common components were selected. The results of the research obtained by the authors will become the basis of further research in the direction of the development of analytical support for social cohesion, adapted to the domestic conditions of the development of society.
Keywords: social cohesion; social capital; integration; social inclusion; measurement